Autonomic denervation dermatitis: A new type of eczematous dermatitis - Bhushan Madke; Madhulika Mhatre; Piyush Kumar; Adarsh Lata Singh; Anil Patki (Wolters Kluwer Medknow Publications, 2017)
We hereby describe a case series of eczematous dermatitis in a peculiar clinical setting. The cases presented with eczematous dermatitis at the site of surgical incision and adjoining skin after a varying lag period. Clinically, all patients presented with xerosis and eczematous rashes around the surgical sites. In our observation, the time taken to develop skin rashes around the surgical sites ranged from 6 months to 3 years. We believe that denervation injury due to dermal nerve transections may lead to autonomic disturbance in the involved area and contribute to the development of dermatitis. Treatment is essentially medical with topical emollients and judicious use of topical corticosteroids. Through this case series, we propose to introduce a new dermatological entity - "autonomic denervation dermatitis" in postsurgical patients.